2011 International Joint Conference on Biometrics (IJCB) 2011
DOI: 10.1109/ijcb.2011.6117509
|View full text |Cite
|
Sign up to set email alerts
|

Competition on counter measures to 2-D facial spoofing attacks

Abstract: Spoofing identities using photographs is one of the most common techniques to attack 2-D face recognition systems. There seems to exist no comparative studies of different techniques using the same protocols and data. The motivation behind this competition is to compare the performance of different state-of-the-art algorithms on the same database using a unique evaluation method. Six different teams from universities around the world have participated in the contest. Use of one or multiple techniques from moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(152 citation statements)
references
References 27 publications
(23 reference statements)
1
151
0
Order By: Relevance
“…It was not until very recently that the problem of spoofing attacks against face biometric system gained attention of the research community. This can be attested by the gradually increasing number of publicly available databases [3][4][5][6] and the recently organized IJCB 2011 competition on countermeasures to 2-D facial spoofing attacks [7] which was the first competition conducted for studying best practices for non-intrusive spoofing detection.…”
Section: Introductionmentioning
confidence: 99%
“…It was not until very recently that the problem of spoofing attacks against face biometric system gained attention of the research community. This can be attested by the gradually increasing number of publicly available databases [3][4][5][6] and the recently organized IJCB 2011 competition on countermeasures to 2-D facial spoofing attacks [7] which was the first competition conducted for studying best practices for non-intrusive spoofing detection.…”
Section: Introductionmentioning
confidence: 99%
“…A recently organized competition on a subset of the PHOTO-ATTACK database called PRINT-ATTACK [30] showed that texture-based methods could potentially beat our proposed method under those conditions. To estimate how well such methods can work against the PHOTO-ATTACK database, we evaluated the work of Chingovska and others [31], a variant of the competition winner based on Local Binary Patterns (LBP), and to which we have access to an open-source implementation 6 .…”
Section: ) Comparison To Texture Approachesmentioning
confidence: 99%
“…However, reflectance and texture analysis-based defense mechanisms have also been proposed against 3D mask attacks [17]- [20]. It is worth noting that many different approaches and design choices have been proposed at the competitions on the countermeasures to presentation attacks [21]- [23].…”
Section: A Presentation Attacks and Defensesmentioning
confidence: 99%